Functional analyses of inclusion membrane proteins of Chlamydia trachomatis - Almeida, Filipe Manuel Baeta da Silva (2019)
Chlamydia trachomatis belongs to a group of highly related obligate intracellular bacteria. It is the etiological agent of important human sexually transmitted infections and trachoma. C. trachomatis strains can be divided in the trachoma biovar, which includes strains that cause noninvasive infections of conjunctival and genital epithelial cells (ocular and urogenital strains, respectively), and the lymphogranuloma venereum (LGV) biovar, which is responsible for a more invasive disease, and includes strains that are able to infect macrophages and disseminate into lymph nodes (LGV strains).